Respuesta :

Answer:

[tex]f(x)= 3({2})^{x} - 3[/tex]

Step-by-step explanation:

Let the equation be of the form

[tex]f(x)= a {b}^{x} + k[/tex]

be the equation, where k=-3 is the horizontal asymptote.

The equation now becomes:

[tex]f(x)= a {b}^{x} - 3[/tex]The curve passes through (0,0)

[tex]0= a {b}^{0} - 3[/tex]

[tex]0 = a - 3[/tex]

a=3

This implies that:

[tex]f(x)= 3{b}^{x} - 3[/tex]

We again substitute (1,3)

[tex]3=3{b}^{1} - 3[/tex]

[tex]3b = 6[/tex]

[tex]b = 2[/tex]

The required equation is

[tex]f(x)= 3({2})^{x} - 3[/tex]

ACCESS MORE